Development of soft skills of students of secondary schools in the process of extracurricular school activities through solving mathematical problems in the game format - Zhukova, O.; Kosogova, A. (Scientific notes of the pedagogical department, 2020)
The relevance of this problem is determined by the need for developing soft skills in modern youth, which include communication, teamwork, leadership, logical thinking, creativity, emotional intelligence, time management, etc. Their formation in secondary school becomes possible in the process of mathematical problems solving in the game format during extracurricular activities. To confirm the state mentioned, we conducted the study using the following methods: generalization, analysis, and systematization of psychology-pedagogical sources on the topic mentioned; survey (respondents – 32 schoolchildren of the 9th grade); pedagogical conversation; prediction. The analysis of the research results made it possible to note that communication, logical thinking and time management became the most foreground soft skills for schoolchildren, which they use in the process of vital activity. Among the most demanded soft skills in conducting mathematics lessons, the respondents emphasized logical thinking, time management, emotional intelligence. Secondary education seekers referred communication, interaction/teamwork skills, creative thinking, leadership, emotional intelligence to the number of most significant soft skills that are necessary for the implementation of extracurricular activities. Among soft skills, which are directly involved in the process of conducting educational activity in mathematics in the game format, the respondents pointed out teamwork, communication, logical and creative thinking, time management, emotional intelligence, leadership. To the number of pedagogical forms, with the help of which the process of formation of soft skills in the educational process, particularly while learning mathematical disciplines, takes place, the majority of schoolchildren referred the club of cheerful and inventive ones, quizzes on the subject, brain-rings. Schoolchildren see the process of soft skills development out of school in using online games, participating in the work of clubs in various educational institutions, attending trainings and speaking clubs. We see the perspectives for the further research in this direction in determining the ways of formation of the skills mentioned in schoolchildren, in the system of lesson activities in conditions of online education.